2020
DOI: 10.1038/s41598-020-79153-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computational chemistry methods for the discovery of quinone-based electroactive compounds for energy storage

Abstract: High-throughput computational screening (HTCS) is a powerful approach for the rational and time-efficient design of electroactive compounds. The effectiveness of HTCS is dependent on accuracy and speed at which the performance descriptors can be estimated for possibly millions of candidate compounds. Here, a systematic evaluation of computational methods, including force field (FF), semi-empirical quantum mechanics (SEQM), density functional based tight binding (DFTB), and density functional theory (DFT), is p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 66 publications
(70 reference statements)
1
52
1
1
Order By: Relevance
“…Given the fact this scheme is also computationally much more demanding, there is no advantage of using it any further. These findings are in accordance with those of the quinone molecules 33 . An overall conclusion is that at the GGA-DFT level (PBE, BLYP), it is possible to use as a descriptor to predict for alloxazines within a range of common experimental errors (i.e.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Given the fact this scheme is also computationally much more demanding, there is no advantage of using it any further. These findings are in accordance with those of the quinone molecules 33 . An overall conclusion is that at the GGA-DFT level (PBE, BLYP), it is possible to use as a descriptor to predict for alloxazines within a range of common experimental errors (i.e.…”
Section: Resultssupporting
confidence: 92%
“…When compared under the same set of approximations, it is observed that: When using in scheme (A), LDA g (R 2 = 0.801, RMSE = 0.035 V) and followed closely by PBE g (R 2 = 0.756, RMSE = 0.039 V) are the two best performing methods. Inclusion of higher order exchange effects and parametrizations, such as in HSE06 and M08-HX, are found to have no positive effect on the prediction accuracies, which is in clear contrast to the case of quinones that have been reported earlier 33 . With in scheme (B) (i.e., a hybrid scheme), PBE s (R 2 = 0.959, RMSE = 0.016 V) emerges as the best performing method and shows a significant improvement over the gas-phase only scheme.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations